2016
DOI: 10.1182/blood-2016-03-705780
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory roles of versican proteolysis in the myeloma microenvironment

Abstract: • Interplay between myeloma niche stromal cells and myeloid cells generates versikine, a novel damageassociated molecular pattern.• Versikine may promote antigen-presenting cell maturation and CD8 1 T-cell activation/recruitment to the tumor bed.Myeloma immunosurveillance remains incompletely understood. We have demonstrated proteolytic processing of the matrix proteoglycan, versican (VCAN), in myeloma tumors. Whereas intact VCAN exerts tolerogenic activities through Toll-like receptor 2 (TLR2) binding, the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 26 publications
8
107
0
3
Order By: Relevance
“…VCAN contributes to cancerous and non-cancerous inflammation by promoting leukocyte-derived elaboration of inflammatory mediators (813) but also immunodeficiency through dendritic cell (DC) dysfunction (14). Interestingly, we also detected in situ VCAN proteolysis in a pattern consistent with the activities of a-disintegrin-and-metalloproteinase-with-thrombospondin-motifs (ADAMTS) proteases (15). We hypothesized that VCAN proteolysis serves to generate bioactive fragments (“matrikines”)(1618).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…VCAN contributes to cancerous and non-cancerous inflammation by promoting leukocyte-derived elaboration of inflammatory mediators (813) but also immunodeficiency through dendritic cell (DC) dysfunction (14). Interestingly, we also detected in situ VCAN proteolysis in a pattern consistent with the activities of a-disintegrin-and-metalloproteinase-with-thrombospondin-motifs (ADAMTS) proteases (15). We hypothesized that VCAN proteolysis serves to generate bioactive fragments (“matrikines”)(1618).…”
Section: Introductionsupporting
confidence: 55%
“…We hypothesized that VCAN proteolysis serves to generate bioactive fragments (“matrikines”)(1618). Indeed, we demonstrated a fragment containing VCAN’s N-terminal 441 amino acids, “versikine” (19), elicits a transcriptional program that is predicted to promote immunogenicity, and thus, antagonize the tolerogenic actions of its parent, intact VCAN (15). However, it is unclear whether VCAN-dependent immunoregulatory mechanisms are operative in non-myeloma, or indeed non-hematopoietic, settings.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hyaluronan fragments can be pro-inflammatory by stimulating inflammatory cytokine release by myeloid cells [165, 166]. The bioactive members of the ADAMTS family of proteases can degrade versican to form versican fragments such as versikine [167] which can be pro-apoptotic in some systems [52] and/or immunoregulatory [168] in other systems. Furthermore, fragments of hyaluronan promote collagen production in some cells [140].…”
Section: Hyaluronan and Versican In Provisional Matrices In Immune Rementioning
confidence: 99%
“…In fact, we found that incubating versican with hyaluronan before adding to activated T lymphocytes inhibited the binding of hyaluronan to the lymphocytes and blocked the migration of T lymphocytes [155]. In addition, versican and versican fragments, like hyaluronan fragments , can bind TLR2 and 4 and induce inflammatory cytokine release from monocytes/macrophages [168, 184192] providing yet another example of how ECM components possess bioactivity and regulate critical events during the early inflammatory response.…”
Section: Hyaluronan and Versican In Provisional Matrices In Immune Rementioning
confidence: 99%
“…Degradation of versican by ADAMTS enzymes during development of mice induces apoptosis in the interdigital tissue and promotes proper limb formation (106). Recently, versican proteolysis and production of the matrikine versikine was found to induce production of the inflammatory cytokines IL-6 and IL-1β in the myeloma microenvironment (107). Given the large number of proteoglycans and glycoproteins that can be present in the ECM in various tissues, there are almost certainly additional matrikines that play important roles in other biological functions that have yet to be identified.…”
Section: Bioactive Ecm Fragments: Matrikinesmentioning
confidence: 99%